Economic policy instruments to increase commuting by bike: Which are the possibilities in Swedish urban areas? - Wennberg, Johanna (My University, 2022)
Urban areas face several increasing sustainable challenges as it is developed for car use. A reduction in urban car use can be achieved by increased bicycle use, which is a goal of the Swedish government. One way of influencing modal choice and travel behaviour is by introducing policy instruments. This thesis aims to investigate which possible economic policy instruments may influence people who live in urban areas in Sweden to change their commuting mode from car to bicycle. The investigation was performed in three parts. Firstly, an initial structural literature review was performed to identify previously tested economic policy instruments to increase biking. The identified economic policy instruments were analysed from the effectiveness, efficiency, equity, and feasibility criteria. Effectiveness assessed possible changes from car to bike use. Efficiency evaluated the effectiveness compared to the societal costs. Equity analysed the effect on different income groups. Feasibility described the eventual practical challenges of the implementations. Lastly, a survey was performed to investigate whether implementing the studied policy instruments could affect mode choice in Swedish urban areas. The respondents’ preference for the policy instrument was analysed through two theoretical models for behavioural change, the theory of planned behaviour (TPB), and the transtheoretical model (TTM), which could partly explain the respondents’ approach to change mode if the economic policy instruments were implemented. The identified economic policy instruments were; subsidised electric bike purchases, subsidised bike-sharing schemes, monetary rewards, increased parking costs, cashout programs, increased driving costs, including increased fuel prices and road pricing, and fare-free public transport (FFPT). The policy instruments recommended for future studies within Swedish urban areas are subsidised electric bike purchases and increased costs for driving and parking. A challenge with these economic policy instruments is the conflict between efficiency and equity which complicates the design of the prices. Applying a policy instrument to the whole population may be efficient but might affect but may put a too significant burden on low-income individuals or reduce the effectiveness by targeting people who do not drive. Further investigations regarding appropriate prices for the identified economic policy instruments are recommended within urban areas considering efficiency and equity.
Keywords: bicycle, economic policy instrument, theory of planned behaviour, transtheoretical model, subsidised electric bike purchase, bike-sharing schemes; parking costs, cash-out, driving costs, fare-free public transportation